Range expansion, density and conservation of the Araucaria Tit-spinetail Leptasthenura setaria (Furnariidae) in Argentina: The role of araucaria Araucaria angustifolia (Araucariaceae) plantations - Cabanne, Gustavo Sebastián (2007)
The Araucaria Tit-spinetail Leptasthenura setaria (Furnariidae) is a globally Near Threatened species. Its habitat, the araucaria (Araucaria angustifolia) rainforest of south-east Brazil and north-east Argentina, is highly fragmented and reduced to nearly 10% of its original range. The species has also been recorded in commercial araucaria plantations that comprise about 80% of its suitable habitat in Argentina. This situation provides an opportunity for the conservation of the Araucaria Tit-spinetail in a human-modified landscape. We assessed the occurrence of the species in the region and estimated its density and total population size in araucaria plantations in Argentina. We discuss the value of plantations in the conservation of the bird, and evaluate its conservation status in Argentina using IUCN criteria. The density of the tit-spinetail in araucaria plantations, estimated by a distance sampling method, was 9 birds ha-1. The overall population size in commercial plantations appears to be large (>7,000 birds), showing that araucaria plantations play an important role in the conservation of the bird. However, plantations must not replace the native araucaria forest because the former are an intrinsically fragmented habitat influenced primarily by economic factors and forestry practices. The long-term conservation and restoration of araucaria rainforest in Argentina and Brazil must be guaranteed to conserve the Araucaria Tit-spinetail and other species associated with this rainforest. Based on the restricted and very fragmented habitat, the Araucaria Tit-spinetail should be regarded as Vulnerable in Argentina.